2009
DOI: 10.1016/j.amepre.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Built Environment for Physical Activity

Abstract: Physical inactivity is one of the most important public health issues in the U.S. and internationally. Increasingly, links are being identified between various elements of the physical-or builtenvironment and physical activity. To understand the impact of the built environment on physical activity, the development of high-quality measures is essential. Three categories of built environment data are being used: (1) perceived measures obtained by telephone interview or self-administered questionnaires; (2) obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
974
3
62

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,081 publications
(1,090 citation statements)
references
References 154 publications
7
974
3
62
Order By: Relevance
“…Beyond objective measures of park characteristics, examining individuals' perceptions of these characteristics is equally important to understanding park visitation and physical activity [24]. Furthermore, some studies show differences between perceived versus objective measures of park characteristics [25][26][27], and perceived measures may be even more important in predicting physical activity and health [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond objective measures of park characteristics, examining individuals' perceptions of these characteristics is equally important to understanding park visitation and physical activity [24]. Furthermore, some studies show differences between perceived versus objective measures of park characteristics [25][26][27], and perceived measures may be even more important in predicting physical activity and health [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as perceptions and meanings of parks can be formed even without having visited [31], understanding nonvisitor residents' perceptions of their neighborhood parks is also important. Most research on perceptions of park characteristics and physical activity has focused on perceptions of access and availability [24,25,29,32]. For example, Hoehner et al [25] found that recreational activity was associated with perceived access to recreational facilities (e.g., parks and walking trails).…”
Section: Introductionmentioning
confidence: 99%
“…Features that make a neighborhood advantageous or disadvantageous can be directly or indirectly assessed via perceptions (Brownson et al, 2009). Tucker et al (2009), who analyzed the relationship between the objectively measured presence of neighborhood recreational opportunities and parental perceptions of those opportunities, showed that both were positively associated with the physical activity of youth.…”
Section: Introductionmentioning
confidence: 99%
“…Administrative data may thus misrepresent participants' contextual exposure at the time of study. Finally, administrative databases do not provide information on some features of interest in health inequalities research such as the quality of neighbourhood features and resources, for example the cleanliness of streets or condition of housing (Brownson et al, 2009). …”
Section: Measuring Neighbourhood Characteristicsmentioning
confidence: 99%
“…Systematic observation involves trained raters going to neighbourhoods (Brownson et al, 2009) or conducting virtual audits with online images (Clarke et al, 2010, Rundle et al, 2011 to rate neighbourhoods on observable features. It helps describe neighbourhoods in terms of the presence, quantity and quality-related characteristics of resources (Brownson et al, 2009). Unlike readily available administrative databases, systematic observation tools can be developed prior to initiating a study.…”
Section: Measuring Neighbourhood Characteristicsmentioning
confidence: 99%